A função constitucional do conhecimento jurídico: em busca de uma nova cultura para o direito - Radaelli, Samuel Mânica (Universidade do Vale do Rio do Sinos, 2007)
The occurred transformations in the Law, provoked for the contemporary constitutionalism establishes new functions to the jurist, in reason of these new functions, the jurist dispense with new abilities that become it apt to its exercise of these new functions. The development of these abilities, by means of legal education, which needs to adopt a transdicipline character, prepared to consolidate a formation that develops in bachelor a theoretical horizon that makes possible it a construction of a new practical, constitutionally adjusted. In this intention the production of legal knowledge can be an important instrument, the measure that of its contribution in the construction of a new legal culture, based for the constitutional dynamics, its proposal ethical-politics and its project of society. This new legal culture of constitutional orientation evokes a new legal practical, which will go reflect it in the daily of the legal life. In reason of this effort in bringing the Constitution for its effectiveness,
Keywords: Brasil; conhecimento; constitucionalismo; constituição; formação profissional; função social; juiz; produção; ensino; constitutional culture; education of the law; legal knowledge; theory of the law; constitutionalism; Ciências Sociais Aplicadas